СПОРТ ШЫНЫҒЫЎЛАРЫНЫҢ САПАСЫН АРТТЫРЫЎДА БРИГАДАЛЫҚ УСЫЛДЫҢ ӘҲМИЙЕТИ - Бекназаров, А.; Қайыпов, Ә. (FAN va JAMIYAT, 2019)
The article is devoted to the analysis of the development and improvement of results in rowing sports in the Republic of Karakalpakstan in 2007-2017 using the Brigade training method. The author of the article recommend using this method in other kinds of sport.